A Concise Review of Spermatogenic Cells Culture: Assessing the Apoptotic Pathway - Silvia Werdhy Lestari (Journal of Global Pharma Technology, 2016)
In the absence of sperm retrieved from azoospermic male, thus considered in utilizing developed spermatogenic cells including spermatogonia to spermatid in restoring male fertility. Spermatogenic cells obtained from testicular tissue culture need to be expanded prior its utilization, yet the excessive apoptosis of resulting cell culture is a challenge. This review was aimed to discuss article dealing with the factors and the underlying mechanism inducing apoptosis of spermatogenic cells culture. A computerized search of PubMed and google scholar database was conducted for general terms such as “male infertility”, “azoospermia”, “human spermatogenesis, “spermatogenic cells” and “apoptosis” and followed by screening and evaluation of collected paper accordingly. Various agents induced the apoptosis in spermatogenic cells such as high temperature, hypothermic storage, metabolite of cell culture derived and gonadotropin suppression driving to apoptosis. Thus all of the agents were paving the specific pathways of inducing apoptosis, through extrinsic and intrinsic, leading to the activation of caspase initiators followed by the activation of caspase executor in various types of spermatogenic cells.Keywords: Human spermatogenic cells, Apoptosis, Culture.